2022
DOI: 10.1126/science.abk2346
|View full text |Cite
|
Sign up to set email alerts
|

Nests of dividing neuroblasts sustain interneuron production for the developing human brain

Abstract: The human cortex contains inhibitory interneurons derived from the medial ganglionic eminence (MGE), a germinal zone in the embryonic ventral forebrain. How this germinal zone generates sufficient interneurons for the human brain remains unclear. We found that the human MGE (hMGE) contains nests of proliferative neuroblasts with ultrastructural and transcriptomic features that distinguish them from other progenitors in the hMGE. When dissociated hMGE cells are transplanted into the neonatal mouse brain, they r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…In support of this scenario, a spectrum of de novo variants in DNMT3A , which overlaps with those found in hematologic malignancies, causes Tatton-Brown-Rahman syndrome, a developmental disorder with macrocephaly ( 27 ). It was also recently shown that human interneurons, in contrast to other neurons, continue to expand until birth ( 28 ). Nonetheless, establishing the cause(s) and extent of the phenomenon of hypermutability requires analysis of larger sets of brains and additional analyses at the single-cell level.…”
Section: Discussionmentioning
confidence: 97%
“…In support of this scenario, a spectrum of de novo variants in DNMT3A , which overlaps with those found in hematologic malignancies, causes Tatton-Brown-Rahman syndrome, a developmental disorder with macrocephaly ( 27 ). It was also recently shown that human interneurons, in contrast to other neurons, continue to expand until birth ( 28 ). Nonetheless, establishing the cause(s) and extent of the phenomenon of hypermutability requires analysis of larger sets of brains and additional analyses at the single-cell level.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, as development progresses, human MGE VZ seems to get thinner and SVZ thicker, with basal neurogenesis becoming dominant after gestational week 10 (Hansen et al, 2013). Moreover, nests of proliferating neuroblasts have been recently reported inside human MGE oSVZ (Paredes et al, 2022). These neuroblasts exhibit sustained proliferation, which can account for the production of the larger number of INs that populate the adult human cortex.…”
Section: Genesis Of Cortical Interneuronsmentioning
confidence: 99%
“…Part c , left panel adapted with permission from ref. 53 , UCSF. Part d , left panel adapted with permission from ref.…”
Section: Neurodevelopment Across Speciesmentioning
confidence: 99%
“…Differences in tissue architecture in the MGE are also important. In humans, this region contains doublecortin-positive cell-enriched nests, which are densely packed islands of immature neurons that contribute to neuron production during the second trimester, thereby increasing interneuron numbers in the human brain 53 (Fig. 2c ).…”
Section: Neurodevelopment Across Speciesmentioning
confidence: 99%